2021
DOI: 10.1111/ffe.13592
|View full text |Cite
|
Sign up to set email alerts
|

An improved fatigue life model for mechanical components considering load strengthening characteristics

Abstract: The small load has fuzziness on the strengthening and damage of the component under the action of random fatigue load. This paper introduces the two-dimensional membership function in fuzzy mathematics to characterize the relationship between stress amplitude, mean value, and damage below the fatigue limit. An exponential function is used to describe the strengthening effect. Under the two-dimensional load spectrum, the influence of various levels on the component's life is comprehensively considered, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…Fatigue damage is the most common failure form of metal structures (Jiang et al. , 2021; Liu et al. , 2021a).…”
Section: Metal Materials Under Impact Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue damage is the most common failure form of metal structures (Jiang et al. , 2021; Liu et al. , 2021a).…”
Section: Metal Materials Under Impact Loadsmentioning
confidence: 99%
“…Based on the finite element analysis, the accuracy of dynamic response is predicted by combining the solid elements, the thick orthotropic metal and composite materials (Liu et al. , 2020a, 2021a). It is shown that a thicker self-reinforcing polypropylene layer in the rear of laminate can improve the impact performance.…”
Section: Nonmetallic Materials Under Impact Loadsmentioning
confidence: 99%
“…In fact, the appearance of the load and the size of the load can be said to be a random process, as shown in Figure 1. In the research stochastic process of load, the whole process is divided into many of the same small process, and the distribution of peak load is recorded, the peak load is regarded as the maximum equivalent load at failure in each time period, and the peak load distribution function is obtained finally 25 . The occurrence and size of the load are randomly varying throughout the process, but the expectation of maximum load is constant, that is to say, the expectation of maximum load in the whole process will not change with time.…”
Section: Gradient Reliability Analysis Methods Considering Strength D...mentioning
confidence: 99%
“…peak load distribution function is obtained finally. 25 The occurrence and size of the load are randomly varying throughout the process, but the expectation of maximum load is constant, that is to say, the expectation of maximum load in the whole process will not change with time. The load model acting on parts is assumed as follows.…”
Section: Description Of the Stochastic Load Processmentioning
confidence: 99%
“…The fatigue crack propagation of storage tank structure is easy to occur under complex loads, and it leads to catastrophic damage. It is of great value and practical engineering significance to study the fatigue crack propagation law and the prediction method of crack growth behavior (Liu et al. , 2022; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%